2020
DOI: 10.1080/00313831.2020.1833237
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Learning Process of Experienced Teachers Focused on Building Positive Interactions with Pupils

Abstract: This work investigated the processes of teacher informal learning focused on building positive teacher-pupil interaction. The conceptual framework "Teacher professional agency for learning" was merged with the "Teaching through interaction" model to compound the exploratory framework of this study: Teachers learn by interacting. Teachers first reported their professional agency through a survey. Next, five high scoring teachers were selected for interview. Final participants accounted being motivated and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(64 reference statements)
1
4
0
1
Order By: Relevance
“…Aspelin's (2019) study, for example, highlighted the importance of socio-emotional skills for teachers. This study's findings also confirm Leite et al's (2022) research, which demonstrated the importance of showing sensitivity, building a positive climate and taking students' perspectives into account. The findings corroborate Hankala´s (2013) study, which showed that teachers' socio-emotional skills are closely intertwined with intrapersonal skills, and these skills are important factors for well-being, coping and adaptability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Aspelin's (2019) study, for example, highlighted the importance of socio-emotional skills for teachers. This study's findings also confirm Leite et al's (2022) research, which demonstrated the importance of showing sensitivity, building a positive climate and taking students' perspectives into account. The findings corroborate Hankala´s (2013) study, which showed that teachers' socio-emotional skills are closely intertwined with intrapersonal skills, and these skills are important factors for well-being, coping and adaptability.…”
Section: Discussionsupporting
confidence: 87%
“…To build positive facilitation to support socio-emotional skills in the classroom, the most applicable strategy is to integrate activities into daily interactions (Thurlings & Brok, 2017). In addition, Leite, Go and Havu-Nuutinen (2022) found in their primary education teacher study that everyday activities of providing emotional support to students are important, such as showing sensitivity, building a positive climate, and considering students' perspectives.…”
Section: Socio-emotional Skillsmentioning
confidence: 99%
“…The instructor guides students in understanding the course topic but also encourages students to ask questions and participate in discussions; Learners receive feedback and encouragement from the instructor, 70 , 71 which in turn influences learners’ self-perceived cognitive and affective learning and increases engagement in online learning. 72 …”
Section: Discussionmentioning
confidence: 99%
“…It addresses and contributes to the learning and teaching process that supports the teacher practices and strategies in professional development. Leite, Go, & Havu-Nuutinen, (2020).…”
Section: On the Significant Relationship Between The Teaching And Lea...mentioning
confidence: 99%